MAHATMA GANDHI’S NOTIONS OF NON-VIOLENCE - Mathew, Bindu (ShodhKosh: Journal of Visual and Performing Arts, 2022)
The philosophy of non-violence or Ahimsa stands as the corner stone of Mahatma Gandhi’s life and work, shaping his social political and spiritual ideologies. This paper tries to discuss the multi-faceted dimensions of Gandhian nonviolence, examining its roots and its practical applications in the freedom movement. It explores how Gandhian political ideologies offered a powerful frame work for resisting oppression without resorting to violence. By analyzing Gandhi’s writings and speeches this paper studies the enduring significance of non-violence as a tool for justice and human dignity.